Photoluminescent properties in quantum-sized structures Cd0,83Zn0.17Te/ZnTe/GaAs of GaAs and AlXGa1-XAs - Sharibaev M; Sayitova S; Najepova S (Genius Journals, 2026)
The change in optical characteristics was determined with the influence of electron and X-ray irradiation in the buffer layers of quantum-sized structures Cd0,83Zn0.17Te/ZnTe/GaAs. Changes in the maxima, bands corresponding to 500 nm and 560-580 nm, associated with transitions on DA pairs, as well as bands I1=2.48 eV (500 nm) and I2=2.21 eV (550 nm) were determined. The I2 band is attributed to a transition associated with intrinsic defects in the ES.
Keywords: Quantum-sized structures; extended defects